Logarithmic asymptotics of the nonlinear Cauchy – Riemann – Beltrami equation - Salimov , R. R.; Stefanchuk , M. V.; Р. Р.; Стефанчук, М. В.; Салімов, Р. Р.; Стефанчук, М. В. (Institute of Mathematics, NAS of Ukraine, 2021)
UDC 517.54; 517.12 We investigate regular solutions of the nonlinear Cauchy – Riemann – Beltrami equation in terms of lower limits and solve an extreme problem for the disk image area functional on a certain class of solutions to the nonlinear Cauchy – Riemann – Beltrami system.